Advances in equine upper respiratory surgery - Hawkins, Jan F. (John Wiley & Sons Inc., 2015)
Advances in equine upper Respiratory surgery is a comprehensive, up-to-date reference on surgical techniques in the upper respiratory tract in the horse, presenting theory and background as well as detailed procedures information.